Essays on speculative financial bubbles - Evripidou, Andria C. (2018)
This thesis contributes to the study of long-run relationships between financial assets. We develop a methodology for testing the hypothesis of co-bubbling behaviour in two series, employing a variant of the stationarity test of Kwiatkowski et al. (1992) which uses a conditional 'wild' bootsrap scheme to control size. We subsequently use our method to test for the presence of co-bubbles in a series of different markets. We look at commodities such as gold and silver and the housing market. There is a plethora of research on the efficacy of unit root tests for detecting explosive rational asset price bubbles. However, the migration of these bubbles and the possibility of co-bubbling behaviour of two series have seldom been researched. In the second chapter of this thesis we apply our model to the commodities market and find that the prices of gold and silver co-bubble in the period following the financial crisis. In the third chapter we investigate the migration of speculative housing bubbles between UK geographic regions. In the third chapter we analyse the co-bubbling relationship between rental and housing prices. We find that an explosive bubble behaviour in rental prices will lead to a bubble behaviour in house prices. The two series co-bubble over a period of time of around two years.